(untitled) (Scientific journal of the Fergana State University, 2025)
The genus Schizothorax represents a group of fish distributed in the mountain rivers of Asia and is distinguished from other cypriniforms by its complex taxonomic history. This article provides a chronological analysis of the research history of Schizothorax species. Between 1832 and 2022, more than 100 species and subspecies were described within this genus; however, over time, the taxonomic status of most of them has changed. At present, 59 of these taxa are considered valid. Furthermore, the article analyzes the current systematic status of the genus Schizothorax, noting the presence of 70 species. It also highlights priority research directions for taxa with complex taxonomic status.